تحسين خدمة المرفق العام على ضوء الإدارة الالكترونية - الدكتــــور قسمية محمد (جامعة المسيلة محمد بوضياف, 2019)
إن توفير الإدارة الإلكترونية في المرفق العمومي كآلية لتحسين الخدمة العمومية خاصة في الجماعات الإقليمية شيء جميل، والشيء الأجمل لو يتم إزالة المعيقات التي تشكل عقبة في تجسيد تلك الإدارة الالكترونية في الميدان، وهذا لا يتأتى إلابتكاتف الجهود من طرف السلطات المختصة ، من أجل توفير متطلبات، منها التشريعات، الدعم الحكومي، الكوادر البشرية، النظم المتطورة، لا سيما نشر ثقافة الإدارة الالكترونية بين المواطنين، لأن تلك الإدارة ليست مثالية لدرجة الكمال وإنما فيها عيوب نسبية تختلف حسب طبيعة كل خدمة وكل نظام في مختلف المجالات، وإذا تم تحقيق المتطلبات المذكورة يمكن القول بأن الإدارة تستطيع مواجهة التحديات والتغيرات المتسارعة ومواكبة التزايد في حجم الخدمات الإدارية المطلوبة. Abstract: The provision of electronic administration in the public facility as a mechanism for improving the public service, especially in the regional groups, is a beautiful thing. The most difficult thing would be to remove obstacles that impede the embodiment of electronic administration in the field. This can only be achieved by concerted efforts by the competent authorities Including the legislation, government support, human resources, advanced systems, especially the dissemination of the culture of electronic management among citizens, because that management is not perfect to perfection, but the relative disadvantages vary according to the nature of each service and each system in various areas, and if the requirement is met Mentioned can be said that the administration can meet the challenges and changes and keep up with the rapid increase in the size of the required administrative services.
Keywords: تحسين /خدمة المرفق العام/ الإدارة الالكترونية